To the workers and peasants of India : manifesto of the Fourth International. - Socialist Workers Party of United States (SWP) (New York : Pioneer Publishers, 1942)
Bibliotheek François Vercammen
Engels
Brochure
Keywords: Vierde Internationale (1938- ).; India